Toward fuzzy temporal databases with temporal fuzzy linguistic terms - Soysangwarn, Sureeporn; Chittayasothorn, Suphamit (My University, 2009)
Fuzzy databases have been proposed by many researchers for handling fuzziness in databases. Fuzzy linguistic terms are used instead of crisp values. They find applications in areas where exact or crisp values cannot always be obtained. In another database research area, temporal databases find applications where facts which are true in the past, as well as facts that will be true in the future are recorded together with current facts. There are also cases where fuzzy databases are also temporal. In most other works, fuzzy facts are temporal or the time itself is fuzzy. This paper presents the concept of a different fuzzy database where fuzzy linguistic terms are temporal. Sample queries and meta tables for temporal similarity degrees and temporal possibility distribution are also presented. ©2009 IEEE.
Keywords: Fuzzy database; Temporal database; Temporal fuzzy terms